Cognitive Workload ≠ Crash Risk: Rejoinder to Study by Strayer et al. (2015). (December 2015) - Shinar, David
Strayer et al.'s article is a significant attempt to scale the cognitive workload of different potentially distracting tasks. It is tempting but not warranted to equate the workload with the relative risk of crash involvement. In this article, I list the reasons why the scaling should not be generalized to safety implications in real driving and argue for the combination of studies of maximal performance assessment (e.g., simulation) with behavioral assessment (e.g., naturalistic driving).